MR Imaging of Transplanted Stem Cells in Myocardial Infarction - Kraitchman, Dara L. (2011)
Recently, several protocols for labeling of stem cells with superparamagnetic iron oxides (SPIOs) have been developed, leading to an active and growing field aimed at visualizing stem cells using MRI (magnetic resonance imaging), including image-guided stem cell injections. This development occurred simultaneously with a significant rise in the number of cell therapy clinical trials for cardiovascular applications and their preceding pre-clinical studies in animal models. In this chapter, we will describe several labeling strategies that can be used to label cells with SPIO nanoparticles. This is followed by a discussion of current strategies for using MRI to visualize these cells in myocardial infarct.